Community readiness and intervention contexts: The case of primary health care social workers in Andalusia (Spain) - Holgado, Daniel; Maya Jariego, Isidro (Anales de Psicología / Annals of Psychology, 2012)
Community readiness refers to the disposition to change con- tingent to social intervention in a community context. In this research, we have evaluated the community readiness of different health contexts. We apply an 18-item scale to 81 social workers of the primary health system in Andalusia (Spain). This scale assesses four dimensions of the community readiness concept: community adjustment, community participation, and implication of social workers and other professionals of the community context. Using Cluster Analysis, 3 key profiles of contexts of intervention were found: a community profile, a welfare profile and a biomedical profile. The results show that from the Community Readiness Model initially proposed by Oetting et al. (1995), it is possible to deepen the community dimension of that concept and use the community context in the definition of the core elements of this model.